Ultima and Worldbuilding in the Computer Role-Playing Game - Kocurek, Carly; Payne, Matthew Thomas (Amherst College Press, 2024)
Ultima and World-Building in the Computer Role-Playing Game is the ﬁrst scholarly book to focus exclusively on the long-running Ultima series of computer role-playing games (RPG) and to assess its lasting impact on the RPG genre and video game industry. Through archival and popular media sources, examinations of fan communities, and the game itself, this book historicizes the games and their authors. By attending to the salient moments and sites of game creation throughout the series’ storied past, authors Carly A. Kocurek and Matthew Thomas Payne detail the creative choices and structural forces that brought Ultima’s celebrated brand of role-playing to fruition.